Effect of Varying Seed Size on Seed Yield and its Contributing Traits in Potato - SUKHDEEP KAUR,; DEEPAK ARORA,; RAJINDER SINGH, (Seed Research, 2026)
The effects of varying seed size on seed yield and its contributing traits in potato were investigated during the years 2015-16 and 2018-19 at University Seed Farm, Ladhowal, PAU, Ludhiana. The objective of the study was to find out the suitable size of seed tubers and intra-row spacing for potato seed production. Four seed sizes viz., < 40 g, 40-70 g, > 70 g and half cuts of tubers Ã100 g were evaluated and the results implicated that the small sized and seed sized tubers gave the best results with respect to tuber length, tuber diameter, tuber volume and tuber weight per plant. The maximum number of tubers per plant was obtained by small sized and cut tubers. The effect of seed sizes were noticed non-significant for average tuber weight. Seed yield was noted maximumwhen small sized tubers (2015-16) and seed sized tubers (2018-19) were used. The total yield was higher when small sized tubers (< 40 g) in 2015-16 and seed sized tubers (40-70 g) in 2018-19 were used. From the present investigation it is evident if small sized tubers were used, the cost of production would be less. Farmer’s practice of using cut tubers for seed production was found more costly and labour intensive as compare to the practice of using small sized tubers.